Meiotic Studies in Some Species of Tribe Cichorieae (Asteraceae) from Western Himalayas - Raghbir Chand Gupta; Henna Goyal; Vijay Singh; Rajesh Kumar Goel (The Scientific World Journal)
The present paper deals with meiotic studies in 15 species belonging to 6 genera of the tribe Cichorieae from various localities of Western Himalayas. The chromosome number has been reported for the first time in Hieracium crocatum (2n=10) and Lactuca lessertiana (2n=2x=16). Further, intraspecific variability has been reported for the first time in H. umbellatum (2n=2x=10 and 2n=6x=54), Tragopogon dubius (2n=2x=14 and 2n=4x=28), and T. gracilis (2n=2x=14). The chromosome report of 2n=2x=10 in Youngia tenuifolia is made for the first time in India. Maximum numbers of the populations show laggards, chromosome stickiness, and cytomixis from early prophase to telophase-II, leading to the formation of aneuploid cells or meiocytes with double chromosome number. Such meiotic abnormalities produce unreduced pollen grains and the reduced pollen viability.